2020
DOI: 10.1021/acs.analchem.9b05562
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Uranium Volatility during Vapor Condensation

Abstract: The predictive models that describe the fate and transport of radioactive materials in the atmosphere following a nuclear incident (explosion or reactor accident) assume that uranium-bearing particulates would attain chemical equilibrium during vapor condensation. In this study, we show that kinetically driven processes in a system of rapidly decreasing temperature can result in substantial deviations from chemical equilibrium. This can cause uranium to condense out in oxidation states (e.g., UO3 vs UO2) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…1 Uranium trioxide is a vapor species under high temperature conditions, making the gas-phase reactivity of UO3 particularly relevant to nuclear material processing and mishaps. 12,13 The T-shaped structure of UO3 has been confirmed by IR spectroscopy in inert matrices, validating the description as bent UO2 2+ coordinated by equatorial O 2-. [14][15][16][17][18] The C2v structure of UO3 contrasts with typical D3h transition metal trioxides with three equivalent oxo groups.…”
Section: Introductionsupporting
confidence: 62%
“…1 Uranium trioxide is a vapor species under high temperature conditions, making the gas-phase reactivity of UO3 particularly relevant to nuclear material processing and mishaps. 12,13 The T-shaped structure of UO3 has been confirmed by IR spectroscopy in inert matrices, validating the description as bent UO2 2+ coordinated by equatorial O 2-. [14][15][16][17][18] The C2v structure of UO3 contrasts with typical D3h transition metal trioxides with three equivalent oxo groups.…”
Section: Introductionsupporting
confidence: 62%
“…Furthermore, plume dynamic modeling of laser ablated uranium suggests higher oxides (e.g., UO 3 ) will form at the outer edge of the plume-atmosphere interface 50 , in agreement with the observed major products here. As previously mentioned, Koroglu et al 23 conclude α-UO 3 is produced when uranium nitrate and O 2 are passed through an ICP and allowed to cool. In that study, the millisecond timescale of reactions may allow for UO 3 to arrange in a crystalline fashion whereas the microsecond timescale of a laser ablation process may only allow amorphous material to form.…”
Section: Discussionmentioning
confidence: 87%
“…One approach to emulate the temperature conditions relevant to study nuclear fireball chemistry in the laboratory is with plasma discharges or high-power lasers 18 23 . Such studies, for instance, have shown the formation of gas-phase UO after laser ablation (LA) of uranium 24 29 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations